Parallelization method for a continuous property - Pilarczyk, Pawel (2010)
An automated method of general purpose is introduced for computing a rigorous estimate of a bounded region in IRn whose points satisfy a given property. The method is based on calculations conducted in interval arithmetic and the constructed approximation is built of rectangular boxes of variable sizes. An efficient strategy is proposed, which makes use of parallel computations on multiple machines and refines the estimate gradually. It is proved that under certain assumptions the result of computations converges to the exact result as the precision of calculations increases. Time complexity of the algorithm is analyzed, and the e effectiveness of this approach is illustrated by constructing a lower bound of the set of parameters for which an overcompensatory nonlinear Leslie population model exhibits more than one attractor, which is of interest from the biological point of view. This paper is accompanied by efficient and flexible software written in C++ whose source code is freely available at http://www.pawelpilarczyk.com/parallel/.